Regional Approach of the European Union in a Potential New Cycle of Enlargement -- a Case Study of the Western Balkans - GJurovski, Marjan; Arnaudov, Mitko (European Studies Department, Jean Monnet Centre of Excellence, Faculty of Philosophy at Sofia University “St. Kliment Ohridski”,Hanns Seidel Foundation, Wilfried Martens Centre for European Studies, 2023)
The political catchphrase Western Balkans has become synonymous for the states and entities in this region which already are in the process of joining the European Union. After Croatia’s membership to the European Union, two approaches have become almost certain: that the European Union will not expand “horizontally” in the medium term and that it is difficult to expect the EU membership of any individual country from the Western Balkans separately from the others, respectively, the assumption of the potential integration of the entire region altogether have become almost universally accepted thesis within political and academic society. In this paper, the key research question is does, in the case of the Western Balkans, the European Union will use the regional approach of integration, i.e., does the entire region will become part of the Union altogether, in the classical sense of understanding full membership in the EU, according to the model of the admission of the countries of Central Europe, i.e., the so-called Visegrad group? From a theoretical point, this paper will provide a contribution to actualising the importance of regionalisation and regional integration in the achievement of foreign policy goals of small and microstates, such as the so-called “six” in the Western Balkans.
Keywords: Western Balkans, European integration, regionalism, membership